Unveiling The Applications of Nanoparticles in Cancer Immunotherapy - Mehra, Gulpreet; Singh, Pragya; Sharma, Nitin (Current Cancer Therapy Reviews, 2025)
Cancer immunotherapy has proven its potential application by enhancing the capacity of the immune system to destroy cancer cells. However, several challenges, such as non-specific targeting, variability in clinical response, and therapeutic resistance, are associated with immunotherapy, making it less efficacious. Nanoparticles (NPs) as a drug delivery system provide additional advantages during immunotherapy by ensuring targeted delivery of antigens. NPs can also change the cancer environment through adjuvant delivery, forcing cancer cells to be destroyed. Here, several applications of NPs are summarized to help enhance the therapeutic values of immunotherapy through several mechanisms. This article outlines the important developments and possible applications of NPs to fully realize the promise of cancer immunotherapy, which will eventually open the door to more personalized and efficient cancer treatments.
Keywords: nanoparticles